2011
DOI: 10.1128/jcm.01303-11
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Death from Systemic Rotavirus Infection and Detection of Nonstructural Rotavirus Proteins

Abstract: A 2.5-year-old girl died suddenly during the course of rotavirus gastroenteritis. The autopsy showed encephalopathy with rotavirus systemic infection. Here, we provide evidence of rotavirus replication in multiple organs. Our findings clarify that rotavirus infection in children can extend beyond the intestinal tract through viremia. CASE REPORTA previously healthy 2.5-year-old girl presented to our hospital following two febrile seizures. She had a 2-day history of diarrhea due to rotavirus gastroenteritis, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…In mammals, rotaviruses are generally recognised to be gastroenteric pathogens of neonates [ 26 ] although the pathogenesis of disease is incompletely understood [ 27 ]. However, there is increasing recognition that infection may be associated with viraemia [ 27 32 ], and disease other than enteritis has been reported in both humans and animals [ 20 , 27 , 33 ] although not yet in birds.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, rotaviruses are generally recognised to be gastroenteric pathogens of neonates [ 26 ] although the pathogenesis of disease is incompletely understood [ 27 ]. However, there is increasing recognition that infection may be associated with viraemia [ 27 32 ], and disease other than enteritis has been reported in both humans and animals [ 20 , 27 , 33 ] although not yet in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Blutt et al (2007) reported that antigenaemia is predictive of viraemia and can be used as a marker of extraintestinal rotavirus involvement. Rotavirus antigen and RNA have been detected in endothelial cells (Cioc & Nuovo, 2002;Morrison et al, 2001), the central nervous system (Nakano et al, 2011), and the liver (Gilger et al, 1992;Nakano et al, 2011) of autopsy cases with fatal rotavirus infection. Because permission for autopsy was not granted in our fatal cases, we could not investigate the relationship between antigenaemia and extraintestinal involvement.…”
Section: P<005mentioning
confidence: 99%
“…Prior to implementation of routine rotavirus immunization, rotavirus gastroenteritis annually caused an estimated 14-60 deaths among children in Europe and the USA (Parashar & Glass, 2006;Van Damme et al, 2006). Infection is mostly localized to the intestine, but severe cases can have extraintestinal involvement, including encephalopathy and sudden death (Ioi et al, 2006;Medici et al, 2011;Minato et al, 1992;Nakano et al, 2011;Salmi et al, 1978). The pathogenesis of these severe infections remains unclear.…”
mentioning
confidence: 99%
“…Rotavirus, a member of the Reoviridae family, is the leading cause of dehydrating diarrhea in children younger than 5 years old worldwide . Fatal encephalopathy with rotavirus systemic infection and virus replication in different organs has been recently reported . Two efficient rotavirus vaccines have been recently introduced, but the age‐restricted recommendation for vaccine administration, the low vaccine coverage, and the low on‐time immunization rates, as well as some logistical problems, are challenging the potential of these vaccines for reducing the risk of death in the poorest countries .…”
mentioning
confidence: 99%
“…1 Fatal encephalopathy with rotavirus systemic infection and virus replication in different organs has been recently reported. 2 Two efficient rotavirus vaccines have been recently introduced, but the age-restricted recommendation for vaccine administration, the low vaccine coverage, and the low on-time immunization rates, as well as some logistical problems, are challenging the potential of these vaccines for reducing the risk of death in the poorest countries. 3,4 Alternative or complementary strategies for preventing or treating rotavirus-associated diarrhea are needed mainly in these countries.…”
mentioning
confidence: 99%